Do direct payments have intertemporal effects on U.S. agriculture? - Roe, Terry L.; Somwaru, Agapi; Diao, Xinshen (International Food Policy Research Institute, 2002)
The question whether production flexibility payments to farmers are likely to be minimally trade distorting is considered in an inter-temporal and economy wide context. Our contribution lies in showing the circumstances, over time, under which a minimally trade distorting result is likely to obtain. If agricultural capital markets are complete, we find that payments have long run effects on land values and land rental rates, but they have no effect on production. If capital markets are not complete, we find production effects, but they are small (0.2 percent) in the short run and disappear in the long-run. The only permanent effects are on land rental rates and land values that increase by about 10 percent in the short run tapering off to slightly above 8 percent in the long run.